Influence of swimming start styles on biomechanics and angular momentum - Vantorre, J.; Seifert, L.; Bideau, B.; Nicolas, G.; Fernandes, R. J.; Vilas-Boas, J. P.; Chollet, D. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Mc Lean et al. in 2000 calculated kinetic momentum generated during block phase for relay`s starts to analyze the quantity of rotation. It was shown that use steps before leaving the block make more steeper takeoff and entry angles. Pike trajectory or arms swing during flight phase can thus have an incidence on body rotation and by consequence on aerial part of the start. The aim of this study was to make a relationship between angular momentum generated during the start and the different start styles. METHODS: Elite swimmers performed 3 times a 25-m at 50-m race pace with preferential start technique. Durations of the block and flight phases, the body angles at take-off and entry, kinetic momentum and standard deviation of it, kinetics and 15m time, were assessed. The sample was classified according to Seifert et al.. Correlations between variables and 15-m time were calculated and ANOVA tests assessed differences between start styles. RESULTS: Performance to 15m were similar between groups. Concerning start variables, take off angle, flight distance, total and standard deviation of angular momentum were significantly lower for flat start by report to the two other start styles. Entry angle was significantly greater for pike start. Vertical impulse was significantly negatively correlated with time to 15m (r=-0.507) and ÄH was positively (r=0.461). DISCUSSION: Lower angular momentum and shorter flight phase for flat start suggest a strategy of reducing aerial phase to go more quickly in the water. Swimmers in flat style reduced temporal deficit instead of trying to travel a higher distance in the air and store higher velocity at water entry for following phases for other styles. Expertise can`t thus be reduce to the accession to a unique technique but optimising with own personal characteristics. Different ways were used: reduce temporal deficit and start to swim early (flat style) or generate high velocity and go farer in the air to travel longer distance and compensate the relative loss of time in following parts of the start (pike and Volkov starts).